(untitled) (Academia Science Repository, 2023)
In this article methodologically substantiated the features of a preschool child, ways of developing monologue speech, and the role of retelling in the development of speech in children. Reading and storytelling with babies and children promotes brain development and imagination, develops language and emotions, and strengthens relationships.